Fifth Five Year Plan (1974-79) A Dimensional Approach - Planning Commission (Planning Commission, 1974)
The strategy of development of Kerala, while conforming to the broad national objectives has to take full account of her special problems and needs and potentialities. The prospects for Kerala's economic advance during the Fifth Plan period are closely linked with the structure and content of the planning proves of the past two decades, the special features of the Slate's economy as well as per resource endowments, both physical and human. During the last twenty-three years of planning in Kerala, the achievements towards rapid economic development have been far from desirable. The State's per capita income continues to be below the ail India level; the industrialisation of the Stale has not made any significant headway; even in the field of agriculture or fisheries, no appreciable improvements in the methods and techniques of production or levels of productivity have been effected.
The State Planning Board